Breeding report of a new blueberry variety Xiangyi - XIONG Rongchuan; YU Weiwei; GONG Xutong; LI Yutong; HAN Jianye; LÜ Zixi; JI Xiangdong; REN Meiyue; ZHANG Tianhui; WANG Hexin; HAN Shiming; XU Guohui (Guoshu xuebao)
The new blueberry variety Xiangyi is a northern highbush variety bred from the natural hybrid seedling of the blueberry variety Patriot. It has large fruit, medium ear density, flat round fruit, thick powder and uniform texture, medium blue color (102-B), medium hardness (3.0 kg·cm-2), average single fruit size of 1.38 cm × 2.02 cm, maximum fruit weight of 3.79 g, and average single fruit weight 2.75 g. The soluble solid content is 12.27%, and the acidity is moderate. The bush is upright, the vigor is medium; The leaves are oblong, the average leaf area is 7.69 cm2, the leaf shape index is 2.04, and the leaf edges are serrated. The beginning of ripening period in the natural state is around late June, belonging to the early maturing varieties. This variety has strong resistance, is suitable for planting in northern Yangtze River or high altitude areas, requiring loose, deep and fertile soil, good drainage, and wet but not waterlogged; The soil texture should be loam or sandy loam, the soil pH 4.0-5.5 is required and organic matter content above 3.0% is better. We found that the characteristics of flowering and fruit, plant growth, fruit quality and fruit yield were consistent. The fruit of this variety is sweet and sour, delicious with thick skin, good flavor, strong fragrance and good yield, being suitable for fresh food varieties, and it can also be processed into jam, fruit juice, fruit wine, fruit vinegar and so on. The land for starting an orchard must be ploughed and leveled, and the ploughing depth is about 20-30 cm. It is advisable to ridge in the direction of south to north, and on irregular hill, the land can be applied by contour planting. It is recommended that the spacing of plants and rows should be 1.5 m×2.0 m. When the soil pH value is greater than 5.5, 200 mesh-300 mesh sulfur powder should be applied to adjust it. Generally, 100 g of sulfur powder is required to reduce 1.0 pH per square meter. When the soil organic matter content is less than 5%, it should be improved by adding an appropriate amount of acidic matrix like turf soil and/or pine needles, so as to adjust it to more than 3%.2 or 3 years old Potted seedlings or bare root seedlings with plant height above 40 cm and main stem base diameter above 0.4 cm should be selected for orchard establishment. The cold resistance capacity of the planting area should reach 600-1200 h or more. The main diseases of blueberries are gray mold and canker. Blueberry pests can cause the plant to grow slowly, and the methods for control include spraying insecticides, biological agents and disinfectants. In the early stage of pest infestation, highly effective, low-toxicity and low-residue chemical pesticides should be applied for prevention and control. The new blueberry cultivar Xiangyi has excellent aromatic traits, delicious fruit flavor, high yield, and prospect for industrial application. It is also an important germplasm resource for improving the aromatic traits of existing blueberry cultivars in China.